The process toward (violent) extremism: an integrated theoretical model using a theory knitting approach - De Pelecijn, Lana (Psychology, crime & law, 2023)
A key challenge within the (violent) extremism research field is building a comprehensive understanding of the process toward (violent) extremism. The lack of overarching models and the fact that explanatory models of (violent) extremism are often isolated/stand-alone, fuels disagreement on how to understand the phenomenon. The goal of this article is to build such an integrated theoretical model that addresses two knowledge gaps within the existing literature: ‘why’ and ‘how’ does an individual become sympathetic to and/or involved in (violent) extremism? Based on a scoping review of 1856 records, we selected ten models of (violent) extremism. These models were then analysed using the ‘theory knitting approach’, searching to identify the overlapping and non-overlapping aspects between the different models. By incorporating the common analysed features and unique contributions of the models, we developed an integrated theoretical model of (violent) extremism as a non-linear and dynamic process model combining an insider and outsider perspective on (violent) extremism.